Historicizing Blake
XII, 188 p.
Keywords: Historicizing Blake puts Blake back into the cultural context of his times. These new essays by both established and younger scholars re-address Blake's contemporary milieu after the neglect of ten years of post-structuralist, reader-orientated, methodology. By employing notions of history wider than the purely 'literary', and featuring an important new essay by the period's foremost subcultural historian, Iain McCalman, Historicizing Blake represents a significant contribution towards the re-historicizing of Romanticism.